The Impact of Technology Media Applications on Aspects of Student Responsibility on Physical Education Learning - Dhani Agusni Zakaria; Sumbara Hambali; Silvy Juditya; Henry Asmara; Sutiswo (UNIB Press, 2023)
This study aims to find out how much impact the use of technology media in the period of limited face-to-face learning has on aspects of student responsibility in Physical Education learning. The method used is to use an ex-post facto quantitative approach. The population in this study was all students at SMKN 10 Bandung, with the samples in this study being class XII Karawitan 1, 2, and 3 students. The sampling technique used the sampling quota technique, and the number of samples in this study was 70 people. The research instrument used is with a questionnaire. The data analysis technique uses percentage analysis calculations with the help of the SPSS for windows version 22 and Microsoft Excel programs. The results of this study show that the impact of the use of PJOK learning technology media during the face-to-face learning period is limited to the aspect of student responsibility that is in the